ONE-PERSON LIMITED LIABILITY COMPANY: CONSIDERING COMPANY’S ORGAN GOVERNANCE OF THE INDONESIAN LEGAL ENTITIES FOR MICRO AND SMALL ENTERPRISES - Kholifah, Ayu; Kurniawan, Shelly (Diponegoro Law Review, 2024)
The government continues to strive to improve the ease of doing business, one of which is legitimizing the existence of a new entity intended for micro and small enterprises (MSEs). The entity is a One-Person Limited Liability Company, which is familiar for particular countries with higher ease of doing business than Indonesia. However, this new business form for MSEs is unique and has different characteristics from other countries. The new regulation restricts the founder and shareholders, who can only be natural persons and cannot be more than one. The problem is that the law obscurity of the company's organ emerges not following previous regulations because there is no obligation to have supervisory bodies on it. Being the only different entity can be an advantage, but it can also be a rash act. This normative legal research uses the comparative law method to identify problems in statutory regulation. The result shows a legal vacuum in the new regulation of Indonesian one-person companies’ organs, whether they should implement the one-tier board or have the option to adopt the two-tier board system. The thing to consider is supervisory bodies should remain within an entity with limited liability regardless of its system.